Duct Stenting vs. Modified Blalock-Taussig Shunt: New Insights Learned From High-Risk Patients With Duct-Dependent Pulmonary Circulation - Mini, Nathalie; Schneider, Martin B. E.; Asfour, Boulos; Mikus, Marian; Zartner, Peter A. (Frontiers in Cardiovascular Medicine, 2022)
Background: As no data is available on the comparison of outcome between modified Blalock-Taussig shunts (MBTs) versus duct-stenting (DS) in patients with pulmonary atresia (PA) and an increased ductal tortuosity and in patients with pulmonary atresia and intact septum (PA-IVS) with right ventricle-dependent coronary circulation (RVDCC), we aimed to perform a single center retrospective evaluation. Methods: between 2010 and 2019 127 patients with duct-dependent pulmonary circulation (DDPC) underwent either MBTs (without additional repairs) (n=56) or DS (n=71). The primary endpoint was defined as arriving at the next planned surgery (Glenn or biventricular repair) avoiding one of the following: 1-unplanned surgery or unplanned perforation of pulmonary valve (PVP) with stent, 2-procedure-related permanent complications and 3-death. Two subgroups were considered: 1: patients who had a ductal curvature index (DCI)> 0.45 (n=32) and 2: patients with PA-IVS and RVDCC (n=13). Ductal curvature index (DCI) was measured in all patients to assess the tortuosity of the ducts. Patients with DCI >0.45 were considered as high-risk group for duct-stenting depending on a previous study showed that patients with DCI< 0.45 had a better outcome comparing with those with DCI> 0.45. Results: The primary outcome was achieved equally in the two groups (77.5% in DS,75% in MBTs). Hospital deaths, need for ECMO and the occurrence of major complications were higher in the group with MBTs with Odds ratio (OR): 5,0.8 and 4 respectively and 95% Confidence Interval (CI): 1.1-22.6 , 0.7-0.9 and 1.6-10.3 respectively. P Value <0.05. For the two subgroups, the primary outcome was achieved in 64% in patients with DCI>0.45 who received MBTs, compared to 20% in those with DS (OR 3.5, 95% CI 1.2-10, p 0.005). While 74.1% of the patients with PA-IVS, RVDCC after DS had achieved the primary outcome, all patients with MBTs had an impaired outcome (OR 3.5, 95%CI 1-11.2, p 0.004). Conclusion: MBTs showed a better outcome in patients with tortuous ducts compared to DS. DS seems to be superior in patients with DDPC with DCI<0.45 and patients with PA-IVS with RVDCC.